2021
DOI: 10.21037/tau-20-913
|View full text |Cite
|
Sign up to set email alerts
|

Optimal acupoint and session of acupuncture for patients with chronic prostatitis/chronic pelvic pain syndrome: a meta-analysis

Abstract: Background: The study aims to perform a meta-analysis of published trials and evaluate the efficacy of acupuncture on chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) by symptom score reduction, optimal acupuncture session, and most frequently used acupoints. Methods: A literature search was performed for randomized controlled trials (RCTs) comparing efficacy of acupuncture with sham acupuncture or standard medication on CP/CPPS. The primary outcome was the reduction of National Institute of Health-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The acupuncture points used in this study are Zhongji (CV3), Guanyuan (CV4), and Dahe (KI12), which are based on our previous study and literature analysis [ 23 , 24 ]. Patients assume a supine position, and acupuncturists use a 75% alcohol cotton ball to sterilize the skin around the acupoints.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acupuncture points used in this study are Zhongji (CV3), Guanyuan (CV4), and Dahe (KI12), which are based on our previous study and literature analysis [ 23 , 24 ]. Patients assume a supine position, and acupuncturists use a 75% alcohol cotton ball to sterilize the skin around the acupoints.…”
Section: Methodsmentioning
confidence: 99%
“…A higher score indicates worse symptoms and vice versa. e severity of CP/CPPS can be graded according to the total scores: mild (1-14), moderate (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), or severe (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Measurement and Outcomesmentioning
confidence: 99%
“…The acupoints used in this study included CV4, CV3, SP6 and BL35 ( Figure 11 ). A meta-analysis showed that these acupoints are the most frequently used acupoints in the clinical treatment of patients with CP/CPPS ( Zhang et al, 2021 ). In terms of Traditional Chinese Medicine (TCM) theory, CV3 and CV4 are acupoints on the Ren Vessel, which have a function of warming Yang and dredging collaterals ( Zheng and Hu, 2017 ; Ying H. Z. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are various methods of acupuncture, such as electric acupuncture (EA) and manual acupuncture (MA). Recent clinical studies have shown that acupuncture promotes efficacy for patients with CP/CPPS relieving pain, urinary symptoms and improving the QOL and NIH-CPSI total score, and the efficacy of acupuncture on CP/CPPS, including anti-inflammatory, neural, and immune modulation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%